Evaluación del comportamiento microbiológico del suelo bajo tres métodos de cobertura y dos formas de nutrición en el cultivo de tomate riñón (Solanum lycopersicum), Alangasí, Quito, Pichincha, 2021 - Morales Alquinga, Mishell Paola (2021)
Microbiological behavior is linked to levels of CO2, which identifies whether the soil contains microbial life, therefore a relationship was established in this study between factors such as: Types of coverages (False clover, rice husk, black plastic and bare soil) and two types of nutrition (Chemical and Organic). An initial microbiological analysis was performed and parameters such as: Temperature, humidity, pH, CFU count in fungi and bacteria were determined by serial solutions of 〖10〗^(-3) and 〖10〗^(-4) . And levels of CO2 of the “Manual of Analytical Methods of the Soil Laboratory 1990”. Analysis of variance was performed in the study for each treatment where there was a significant difference in turkey at 5%. %. It was determined that the temperature on a larger scale was the coverage of black plastic with 22.39 ºC, in terms of humidity it had a significance with the types of coverage obtaining that the treatments of black plastic and rice husk belong to a group A of higher humidity; The pH variable did not show significance; the CFU count in fungi had a greater scale of development in the coverages of false clover and rice husk, in terms of the CFU in bacteria the group of greatest significance was false clover plus organic nutrition; The levels of CO2 tube significance in treatments 1 and 2 of false clover with 7.22 gr CO2 for each 100 gr of soil in group A. Finally, in the correlation table between the levels of CO2 and the population of fungi a 0.6 influence, and with relation to the bacteria 0.27.